Her Dark Materials: What Makes the Fantastic Dark - Limpár, Ildikó (Hungarian Journal of English and American Studies, 2022)
Book review: Thomas, Ebony Elizabeth. The Dark Fantastic: Race and the Imagination from Harry Potter to The Hunger Games. New York UP, 2020. 240 pages. ISBN 9781479806072. Pbk. 16.95.